A Struwe Type Decomposition Result for a Singular Elliptic Equation on Compact Riemannian Manifolds (Analysis in Theory and Applications, 2018)
On a compact Riemannian manifold, we prove a decomposition theorem for arbitrarily bounded energy sequence of solutions of a singular elliptic equation.
Keywords: Yamabe equation; critical Sobolev exponent; Hardy inequality; bubbles.